Patient feedback questionnaires to enhance consultation skills of healthcare professionals: A systematic review. Issue 9 (September 2018) - Al-Jabr, Hiyam; Twigg, Michael J.; Scott, Sion; Desborough, James A.
Highlights: Several patient feedback questionnaires are available. Most patient feedback questionnaires are designed specifically for physicians. Patient feedback questionnaires need to be validated with different practitioners. Patient feedback can help in enhancing consultation skills of practitioners. Abstract: Objective: To identify patient feedback questionnaires that assess the development of consultation skills (CSs) of practitioners. Methods: We conducted a systematic search using seven databases from inception to January 2017 to identify self-completed patient feedback questionnaires assessing and enhancing the development of CSs of individual practitioners. Results were checked for eligibility by three authors, and disagreements were resolved by discussion. Reference lists of relevant studies and Open Grey were searched for additional studies. Results: Of 16, 312 studies retrieved, sixteen were included, describing twelve patient feedback questionnaires that were mostly designed for physicians in primary care settings. Most questionnaires had limited data regarding their psychometric properties, except for the Doctor Interpersonal Skills Questionnaire (DISQ). Most studies conducted follow-up, capturing positive views of practitioners regarding the process (n = 14). Feedback was repeated by only three studies, demonstrating different levels of improvement in practitioners' performance. Conclusion: Identified questionnaires were mainly focused on physicians, however, to support using patient feedback, questionnaires need to be validated with other practitioners. Practice implications: Several patient feedback questionnaires are available, showing potential for supporting practitioners' development. Valid questionnaires should be used with appropriate practitioners in developing more evidence for the impact they may have on actual consultations.